Rip current occurrence probability at selected recreational beaches along Pahang coastline - Hamsan, Muhammad Amirul Syafiq; Ramli, Muhammad Zahir (Emerald Group Publishing, 2020)
Pahang beaches draw more than thousand visitors throughout the year. From the year 2006 to 2018, more than 30 drowning and near-drowning cases were recorded mainly from rip currents. Rip currents define as unexpected current that carried beachgoers away to seaward direction more than ~ 50 meters from shore. The prediction of rip current development is very important for protection of human life. In this study, preliminary survey and field works were carried out to identify rip current hazards. The output would be an early warning preventative mitigation to public in Pahang. Beach state model, dimensionless fall velocity, (Ω), littoral environment observation (LEO) and relative tidal range (RTR) were recorded for five recreational beaches during two different months (March and April 2018). The morphodynamic parameters such sediment fall velocity (Ws), sediment grain size (D50), beach slope are then analysed using software PROFILER. Classification of risks were done based on beach morphodynamic model (Ω-RTR). The morphodynamics are classified as low tide bar rip (LTBR), barred (B), low tide terrace associated with rip current (LTTR), bar dissipative (BD), reflective (R), non-bar dissipative (NBD), low tide terrace (LTT) and ultra-dissipative (UD). Result shows three out of five recreational beaches may develop high risk rip currents. During the first month of survey, Batu Hitam (BH) recorded the only one recreational beach that may develop high risk rip current followed by Teluk Cempedak (TC) and Kempadang (KEM) as middle risk rip current beach while Balok (BA) and Sepat (SEP) as low risk rip current beach. Different during second month of survey, Balok (B), Batu Hitam (BH) and Sepat (SEP) were recorded as high risk rip current beach while Teluk Cempedak (TC) and Kempadang (KEM) as low risk rip current beach. The results are consistent with beach incidents (drowning and near-drowning) reported.